Pendampingan Penyusunan Tes Bahasa Arab Berdasarkan Standar Kognitif Bloom Menggunakan Platform Classmarker Untuk Pengajar Mutholaah Pondok Modern Darussalam Gontor Putri Kampus 1 - Rochma, Siti Nikmatul; Mahmudi, Ihwan (LPPM UMRI, 2026)
This community service program aims to enhance the competence of muṭāla‘ah teachers in developing Arabic language assessment instruments based on Bloom’s cognitive taxonomy and integrating them into digital evaluation using the ClassMarker platform. The program was initiated due to the dominance of low- to medium-order thinking questions in muṭāla‘ah assessments, which limits the development of students’ higher-order thinking skills. A participatory-educational approach was employed, consisting of needs analysis, conceptual socialization of Bloom’s taxonomy, HOTS-based test item development training, and hands-on assistance in using ClassMarker. Data were collected through observation, group discussions, pre-test and post-test assessments, and analysis of the test items produced by participants. The results indicate an improvement in teachers’ understanding of Bloom’s cognitive levels, enhanced ability to design HOTS-based muṭāla‘ah questions (C3–C6), and increased proficiency in operating ClassMarker for digital assessment. This program contributes to improving the quality of Arabic language assessment that is more objective, efficient, and data-driven within the pesantren educational context.